Kedudukan Hasil Audit Investigatif Pada Kekayaan Badan Usaha Milik Negara Persero Dalam Hukum Pembuktian Pidana di Indonesia - Susanto Susanto (Jurnal Cita Hukum, 2018)
Abstract:Entering the era of globalization, several state-owned enterprises have improved management, particularly the efficiency of operations in order to be able to face market competition. The improvement measures taken include business restructuring, reduction in the number of employees, implementation of management control systems, and other strategic policies. State-owned enterprises that do not improve management will usually face various difficulties, especially in the financial sector. In the legal process of calculating state losses caused by mistakes of State-Owned Enterprises, an investigative audit is required, because investigative audits can be used to determine whether or not there is a Law Against Acts, mains read and abuse of authority that results in state losses as the majority shareholder in the Owned Enterprise Country. The position of the investigative audit results on State-Owned Enterprises in the Indonesian legal system of proof is; As a statement of the witness, as a proof of letter, as evidence of expert testimony, as evidence of guidance, as evidence of indicated / suspected evidence.Keywords: Investigative Audit, State-Owned Enterprise, Evidence Abstrak:Memasuki era globalisasi, beberapa BUMN telah melakukan perbaikan manajemen, khususnya efisiensi operasi agar mampu menghadapi persaingan pasar. Langkah perbaikan yang dilakukan meliputi restrukturisasi usaha, pengurangan jumlah karyawan, penerapan sistem pengendalian manajemen, dan kebijakan strategis lainnya. BUMN yang tidak melakukan perbaikan manajemen, biasanya akan menghadapi berbagai kesulitan, terutama di bidang finansial. Dalam proses hukum menghitung kerugian negara yang diakibatkan kesalahan Badan Usaha Milik Negara, diperlukan audit investigatif, karena audit investigatif bisa digunakan untuk mengetahui ada atau tidaknya Perbuatan Melawan Hukum, mains read dan penyalahgunaan wewenang yang mengakibatkan adanya kerugian negara selaku pemegang saham mayoritas pada Badan Usaha Milik Negara. Kedudukan hasil audit investigatif pada Badan Usaha Milik Negara dalam sistem hukum pembuktian Indonesia adalah; Sebagai Keterangan Saksi, Sebagai alat bukti surat, Sebagai alat bukti keterangan ahli, Sebagai bukti Petunjuk, Sebagai alat bukti keterangan Terindikasi/Terduga.Kata Kunci: Audit Investigatif, Badan Usaha Milik Negara, Pembuktian